(untitled) (Urdimento - Revista de Estudos em Artes Cênicas, 2026)
This article addresses reenactment as a bodily critique of the archive, a rupture of linear temporality, and a catalysing act of return that values ​​both the unrepeatable and the enduring. It is also viewed as a tool for revisiting unresolved issues in performance practice and as an operation that reactivates political tensions, embodied memories, and historical resonances. Insights from Peggy Phelan, Rebecca Schneider, Diana Taylor, and Leda Martins frame reenactment as a process of transforming meaning through variations in bodies, spaces, and contexts, thereby generating new forms of knowledge production.